Проблема Преодоления Психологического Барьера Студентами Неязыковых Вузов При Изучении Русского Языка Как Иностранного - Оринбаева Сайёра Юсуповна (Periodica Journal, 2024)
This article examines the problem of psychological barriers among students of non-linguistic universities when studying Russian as a foreign language. Some ways to overcome them are also proposed.
Keywords: Russian; language; overcome